Sistem Pakar dengan Metode Backward Chaining untuk Optimalisasi Layanan Helpdesk E-Government - Hariona, Popi (SAFE-Network, 2021)
The e-Government helpdesk service is an assistance service to deal with user needs related to disturbances and problems that occur both infrastructure and networks, applications and information systems as well as information security that occur in the Payakumbuh City Government. At this time most of the complaints that come to the front office helpdesk always need technicians to handle them, despite the limited number of technicians for handling e-Government problems in Payakumbuh City. This study aims to optimize e-Government Helpdesk services so that services can be carried out without direct technician intervention. The data used in this research is the disturbance report data that goes to the e-Government helpdesk service of Payakumbuh City during the last 11 months from 33 Regional Devices in Payakumbuh City and the stages of problem solving by technicians. This study uses the backward chaining method to identify the causes of disruption to e-Government services. The results achieved in this study are as many as 21 rules that can be applied directly to helpdesk services, with an accuracy rate of 92%. The rules generated by the backward chaining method can be used to optimize the resolution of disturbances that enter the helpdesk by the front office without waiting for the technician.